A eukaryotic enzyme that can disjoin dead-end covalent complexes between DNA and type I topoisomerases. - Yang, S W (1996)
The covalent joining of topoisomerases to DNA is normally a transient step in the reaction cycle of these important enzymes. However, under a variety of circumstances, the covalent complex is converted to a long-lived or dead-end product that can result in chromosome breakage and cell death. We have discovered and partially purified an enzyme that specifically cleaves the chemical bond that joins the active site tyrosine of topoisomerases to the 3' end of DNA. The reaction products made by the purified enzyme on a variety of model substrates indicate that the enzyme cleanly hydrolyzes the tyrosine-DNA phosphodiester linkage, thereby liberating a DNA terminated with a 3' phosphate. The wide distribution of this phosphodiesterase in eukaryotes and its specificity for tyrosine linked to the 3' end but not the 5' end of DNA suggest that it plays a role in the repair of DNA trapped in complexes involving eukaryotic topoisomerase I.